Incidence of first stroke and ethnic differences in stroke pattern in Bradford, UK: Bradford Stroke Study. Issue 4 (June 2018) - Ramadan, Hawraman; Patterson, Chris; Maguire, Stuart; Melvin, Ian; Kain, Kirti; Teale, Elizabeth; Forster, Anne
Background: Information on ethnic disparities in stroke between White and Pakistani population in Europe is scarce. Bradford District has the largest proportion of Pakistani people in England; this provides a unique opportunity to study the difference in stroke between the two major ethnic groups. Aim: To determine the first-ever-stroke incidence and examine the disparities in stroke patterns between Whites and Pakistanis in Bradford. Methods: Prospective 12 months study consisting of 273, 327 adults (≥18 years) residents. Stroke cases were identified by multiple overlapping approaches. Results: In the study period, 541 first-ever-strokes were recorded. The crude incidence rate was 198 per 100, 000 person-years. Age adjusted-standardized rate to the World Health Organization world population of first-ever-stroke is 155 and 101 per 100, 000 person-years in Pakistanis and Whites respectively. Four hundred and thirty-eight patients (81%) were Whites, 83 (15.3%) were Pakistanis, 11 (2%) were Indian and Bangladeshis, and 9 (1.7%) were of other ethnic origin. Pakistanis were significantly younger and had more obesity ( p = 0.049), and diabetes mellitus (DM) ( p = <0.001). They were less likely to suffer from atrial fibrillation ( p = <0.001), be ex- or current smokers ( p = <0.001), and drink alcohol above the recommended level ( p = 0.007) compared with Whites. In comparison with Whites, higher rates of age-adjusted stroke (1.5-fold), lacunar infarction (threefold), and ischemic infarction due to large artery disease (twofold) were found in the Pakistanis. Conclusions: The incidence of first-ever-stroke is higher in the Pakistanis compared with the Whites in Bradford, UK. Etiology and vascular risk factors vary between the ethnic groups. This information should be considered when investigating stroke etiology, and when planning prevention and care provision to improve outcomes after stroke.